Determinants of demand for subsequent doses of pneumococcal and rotavirus vaccines for children less than five years of age in Ghana - Immurana, Mustapha; U., Arabi (International Journal of Health, 2016)
The mortality of children which has pneumonia and diarrhoea as some of its major causes remains a major concern for all countries of which Ghana is no exception. Ghana’s current child mortality rate is far above the sustainable development goal 3.2. However, given that vaccination is one of the most effective ways of preventing childhood diseases, it was surprising that, the 2014 Ghana demographic and health survey (GDHS) report showed a falling up-take or coverage in the successive doses of the pneumococcal (pneumonia vaccine) and rotavirus (diarrhoea vaccine) vaccines among children in Ghana. This study therefore using data from the children’s recode file of the 2014 GDHS, investigated the determinants of demand for subsequent doses of the pneumococcal and rotavirus vaccines for children in Ghana by employing the binary probit model. The study among other findings revealed that, unemployed mothers were less likely to demand for the subsequent and initial doses of both the pneumococcal and rotavirus vaccines for their children. Also male household heads were revealed to be less likely to demand for all the doses of the rotavirus vaccines for children. In addition, single mothers were also revealed to be less likely to demand for all the subsequent doses of the pneumococcal and rotavirus vaccines. Therefore targeting unemployed and single mothers as well as women empowerment through job opportunities coupled with public education, especially of household heads, would serve as effective tools in tackling the falling demand for subsequent doses of the pneumococcal and rotavirus vaccines for children in Ghana.